Mirtazapine blood levels and antidepressant response - De Donatis, Domenico; Verrastro, Marco; Fanelli, Giuseppe; Fabbri, Chiara; Maniscalco, Ignazio; Hart, Xenia Marlene; Schoretsanitis, Georgios; Mercolini, Laura; Ferri, Raffaele; Lanuzza, Bartolo; Serretti, Alessandro; Conca, Andreas; et al. (International journal of psychiatry in clinical practice, 2024)
Therapeutic drug monitoring (TDM) is an important tool for treatment optimisation. Its usefulness has recently been demonstrated for some first-line antidepressants; however, few studies have been reported on the relationship between blood levels of mirtazapine and its antidepressant effects. The aim of this study was to investigate the association between blood concentration of mirtazapine and antidepressant response. 59 outpatients treated with mirtazapine for depression were recruited and followed up for three months in a naturalistic setting. Hamilton Depression Rating Scale-21 (HAMD-21) was administered at baseline, month 1, and month 3 to assess antidepressant response. Mirtazapine serum concentration was measured at steady state. Linear regression analysis and nonlinear least-squares regression were used to estimate association between serum concentration of mirtazapine and antidepressant response. Our results showed no overall association between serum concentration of mirtazapine and symptom improvement at month 1 and month 3. A marginally significantly higher serum concentration of mirtazapine was found in responders vs non-responders at month 3. The study suggests that serum concentration of mirtazapine is not strongly associated with the antidepressant efficacy of mirtazapine. This is probably attributed to its pharmacodynamic profile, even though higher blood levels seem to be marginally more effective. Mirtazapine plasma levels association with response is mild and do not follow the same curve of other antidepressants Mirtazapine higher plasma levels may show some benefit in a subgroup of patients Therapeutic drug monitoring may help during antidepressant treatment